The responses of eosinophil and packed cell volume (PCV) on sheep infected with Fasciola gigantica - S Widjajanti; S Endah Estuningsih; Subandriyo Partoutomo; H.W Raadsma; T.W Spithill; D Piedrafita (Indonesian Center for Animal Research and Development (ICARD), 2002)
The responses of eosinophil and packed cell volume (PCV) values were verified in infected sheep, in order to identify whether these parameters could be used to predict the flukes burden and their correlation with breed resistance. Fifteen Indonesian thin tail sheep (ET), 9 Merino sheep and 148 backcross sheep generated from mating of Merino sheep and F1 sheep (Merino X ET cross) were infected with 300 metacercariae of Fasciola gigantica. The blood samples were collected every 2 weeks by using EDTA venoject tubes in order to determine the amount of eosinophils and the PCV value. After 14 weeks of infection all of sheep were killed and the liver was collected in order to determine the number of flukes. The results showed that the amount of eosinophils increased 2 weeks after infection and reached the peak at week 4 after infection. The average of eosinophils in ET appeared higher than the other 2 breeds (Merino was the lowest and the backcross was in between). The correlation between the number of flukes recovered from the liver and the eosinophil counts were positive in ET and Merino, but negative in the backcross sheep. The PCV values remained constant along the trial, except at week 14 after infection; the PCV values were slightly decreased in backcross sheep and Merino sheep, but not in ET sheep. The correlation between number of flukes in the liver and the PCV values were negative in all breeds of sheep. These results suggested that the eosinophilic and PCV’s response of ET were higher compared to backcross and Merino sheep, thus that responses were thought to be associated with the resistant phenomenon. Key words: Fasciolosis, eosinophil, PCV, sheep